New record of the genus Buluka de Saeger (Hymenoptera: Braconidae: Microgastrinae) with description of a new species from Vietnam - Long, Khuat Dang (Academia Journal of Biology, 2015)
Buluka de Saeger, 1948, is a rare genus of the subfamily Microgastrinae, in this paper one new species of the genus, Buluka vuquangensis Long, sp. n., is described and illustrated. Additionally, the genus Buluka de Saeger is recorded for the first time for Vietnam